Morphological and Compositional Analysis on Thermal Deposition of Supercritical Aviation Kerosene in Micro Channels - Ao Sun; Cui Ye; Chenyang Yao; Lifeng Zhang; Ji Mi; Wenjun Fang (Molecules, 2023)
The integration of active cooling systems in super or hypersonic aircraft using endothermic hydrocarbon fuels is considered an effective way to relieve the thermal management issues caused by overheating. When the temperature of aviation kerosene exceeds 150 °C, the oxidation reaction of fuel is accelerated, forming insoluble deposits that could cause safety hazards. This work investigates the deposition characteristic as well as the morphology of the deposits formed by thermal-stressed Chinese RP-3 aviation kerosene. A microchannel heat transfer simulation device is used to simulate the heat transfer process of aviation kerosene under various conditions. The temperature distribution of the reaction tube was monitored by an infrared thermal camera. The properties and morphology of the deposition were analyzed by scanning electron microscopy and Raman spectroscopy. The mass of the deposits was measured using the temperature-programmed oxidation method. It is observed that the deposition of RP-3 is highly related to dissolved oxygen content (DOC) and temperature. When the outlet temperature increased to 527 °C, the fuel underwent violent cracking reactions, and the structure and morphology of deposition were significantly different from those caused by oxidation. Specifically, this study reveals that the structure of the deposits caused by short-to-medium term oxidation are dense, which is different from long-term oxidative deposits.